Anti-Racist Assessment in Religious Studies and Biblical Studies Classes - Jones, Christopher M. (Teaching theology and religion, 2025)
The persistent achievement gap between Black and white students in U.S. higher education demands the attention of anti-racist educators. This essay advances two interconnected arguments. First, I argue that the achievement gap represents yet another manifestation of the denial of opportunities for Black families to build and transfer intergenerational wealth in the U.S. Second, I contend that the predominance of Eurocentric, secular methodologies in religious studies and biblical studies classrooms perpetuates anti-Blackness, thereby disadvantaging Black students and deepening the achievement gap. These threads converge in the realm of student assessment, where I argue that U.S. grading systems inadequately capture the knowledge and skills Black students acquire, perpetuating the perception that they are underperforming academically and materially depriving them of the benefits of college degrees.